Screening Outcomes Following Implementation of Digital Breast Tomosynthesis in a General-Population Screening Program - McCarthy, Anne Marie; Kontos, Despina; Synnestvedt, Marie; Tan, Kay See; Heitjan, Daniel F.; Schnall, Mitchell; Conant, Emily F. (JNCI : Journal of the National Cancer Institute, 2014)
Early data on breast cancer screening utilizing digital breast tomosynthesis (DBT) combined with digital mammography (DM) have shown improvements in false-positive and false-negative screening rates compared with DM alone. However, these trials were performed at sites where conventional mammographic screening was concurrently performed, possibly leading to selection biases or with complex, multireader algorithms not reflecting general clinical practice. Our study reports the impact on screening outcomes for DBT screening implemented in an entire clinic population. Recall rates, cancer detection, and positive predictive values of screening were compared for 15571 women screened with DBT and 10728 screened with DM alone prior to DBT implementation at a single breast imaging center. Generalized linear mixed-effects models were used to estimate the odds ratio (OR) for recall rate adjusted for age, race, presence of prior mammograms, breast density and reader. All statistical tests were two-sided. DBT screening showed a statistically significant reduction in recalls compared to DM alone. For the entire population, there were 16 fewer recalls (8.8% vs 10.4%, P <.001, adjusted OR = 0.80, 95% confidence interval [CI] = 0.74 to 0.88, P < .001) and 0.9 additional cancers detected per 1000 screened with DBT compared to DM alone. There was a statistically significant increase in PPV1 (6.2% vs 4.4%, P = .047). In women younger than age 50 years screened with DBT, there were 17 fewer recalls (12.3% vs 14.0%, P = .02) and 3.6 additional cancer detected per 1000 screened (5.7 vs 2.2 per 1000, P = .02). Our data support the clinical implementation of DBT in breast cancer screening; however, larger prospective trials are needed to validate our findings in specific patient subgroups.